Open and Arthroscopic Surgical Treatment of Femoroacetabular Impingement - Kuhns, Benjamin D.; Frank, Rachel M.; Pulido, Luis (Frontiers in Surgery, 2015)
Femoroacetabular impingement (FAI) is a common cause of hip pain, and when indicated, can be successfully managed through open surgery or hip arthroscopy. The goal of this review is to describe the different approaches to the surgical treatment of FAI. We present the indications, surgical technique, rehabilitation, and complications associated with (1) open hip dislocation, (2) reverse peri-acetabular osteotomy, (3) the direct anterior “mini-open” approach, and (4) arthroscopic surgery for femoroacetabular impingement.